Hubungan Hasil Belajar Rias Wajah Sehari-Hari dengan Minat Menjadi Makeup Artist pada Siswa Kelas X SMKN 7 Kota Tangerang Selatan - Lidya Jesika Sinaga; Mari Okatini Armandari; Neneng Siti Silfi Ambarwati (Departement of Mathematics Education, 2024)
Learning outcomes are a benchmark for the success of a learning activity. Good learning outcomes can make it easier for students to develop their potential in a certain field. Interest in becoming a makeup artist is a concentration of attention that contains elements of attention, pleasure, heart tendencies, and an unintentional desire that is active in accepting from the environment to become a makeup artist. This study aims to determine the relationship between daily makeup learning outcomes and interest in becoming a makeup artist. This research was conducted on class X students majoring in skin and hair beauty at SMKN 7 South Tangerang City, academic year 2023/2024. The research method used is quantitative associative with a correlational approach. The population in this study is all 77 students of class X with a sampling technique, namely total sampling. The instrument used to obtain interest data was measured using a questionnaire with a Likert scale. Learning outcomes use secondary data, namely grades from daily make-up subjects obtained by students in odd semesters. The data analysis method uses Spearman correlation. Data analysis was assisted through SPSS software version 29. The research results obtained a significant value of 0.06 > 0.05, which means that learning outcomes do not have a significant relationship with interest in becoming a makeup artist..